Galectin‐3 and histological, molecular and biochemical aspects of myocardial fibrosis in heart failure of hypertensive origin. (11th February 2015) - López, Begoña; González, Arantxa; Querejeta, Ramón; Zubillaga, Elena; Larman, Mariano; Díez, Javier
<x xml:space="preserve">Abstract</x> Aims The aim of this study was to investigate whether galectin‐3 (Gal‐3) is associated with myocardial histological and molecular parameters related to fibrosis and with the circulating biomarkers of the extracellular generation of mature fibril‐forming collagen types I (C‐terminal propeptide of procollagen type I, PICP) and III (N‐terminal propeptide of procollagen type III, PIIINP) in two independent studies of hypertensive patients with heart failure (HF). Methods and results Endomyocardial biopsies and blood samples from 39 HF patients (invasive study), and blood samples from 220 HF patients (non‐invasive study) were analysed. Necropsies (n = 7) and blood samples (n = 20) from healthy subjects were used as controls. In the invasive study myocardial mRNA and protein expression of Gal‐3 and collagen types I and III, plasma Gal‐3 and serum PICP and PIIINP were all significantly increased in patients compared with controls. Neither myocardial nor plasma Gal‐3 were correlated with myocardial collagen and circulating biomarkers; whereas PICP was correlated with myocardial total (r = 0.819, P < 0.001) and collagen type I (r = 0.744, P < 0.001) deposition, PIIINP was not. In the non‐invasive study both plasma Gal‐3 and serum PICP were increased (P < 0.001) in patients compared with controls. No correlation was found between Gal‐3 and PICP in HF patients. Conclusions These findings show that although an excess of cardiac and systemic Gal‐3 is present in patients with HF of hypertensive origin, this molecule is not associated with histological, molecular and biochemical parameters related to myocardial fibrosis in these patients.